(Re)Testing the 'follow the customer' hypothesis in multinational bank expansion - Esperança, J.; Gulamhussen, M. A. (Journal of Multinational Financial Management, 2001)
Theory suggests that multinational banks follow their corporate and non-corporate customers. Previous empirical studies have tested the hypothesis that multinational banks follow their corporate customers. This study bridges a gap between the theory and previous empirical studies by testing the hypothesis that multinational banks also follow their non-corporate customers. We accomplish the purpose by empirically testing a model of the effect of home country factors on multinational bank expansion. Our results support the hypothesis that multinational banks also follow their non-corporate customers.